The Antioxidant Content and Activity of Various Plant Organs of Kitolod (Isotoma longiflora) - Grahita Rezhi Egarani; Sri Kasmiyati; Elizabeth Betty Elok Kristiani (Biosaintifika: Journal of Biology & Biology Education, 2020)
Antioxidants play a crucial role in human health owing to their ability to neutralize oxidative reactions. Kitolod (Isotomalongiflora) is one of the medicinal plants that can be used as a source of antioxidant. The aim of study wasto compare the content of antioxidant compounds (flavonoids, phenolics, chlorophylls, carotenoids, and ascorbic acid) in various organs of the kitolod plant. The plant organs studied includingroots, stems, leaves, flowers, and fruits. The extraction of each plant organ wasconducted by maceration technique using ethanol as a solvent at the room temperature for 48 hours. The analysis of total flavonoids, phenolics, and ascorbic acid was performed by colorimetry method using AlCl3, Folin, and sulfosalicyclic acid reagent respectively, while chlorophylls and carotenoids was determined by direct colorimetry method with methanol as a solvent. The antioxidant activity of various plant organs of kitolod was analyzed using the DPPH method. The highest total flavonoid, phenolic, chlorophyll, and carotenoid compounds werefound in leaves, respectively by 10.48, 1.46, 7.25, and 56.98 ppm. The highest ascorbic acid content and antioxidant activity were obtained fromfruits.The research findings provide new and important information aboutthe contents and antioxidant activity of the secondary metabolites (flavonoid, phenolic, chlorophyll, carotenoid, and ascorbic acid) in each organ of kitolod plant. The information from the results of this study can be used to increase the medicinal value ofkitolod plants.